Heimlich Valve as an Ambulation Management of Persistent Pneumothorax or Fluidopneumothorax - Faradila Nur Aini; Irmi Syafa'ah (Faculty of Medicine Universitas Airlangga, 2021)
Pneumothorax or fluidopneumothorax is a critical condition when there is some air or/and fluid in the plural cavity. The symptoms may include shortness of breath, chest pain, blue discoloration of the skin or lips, increased heart rate, and loss of consciousness. Pleural cavity drainage is management therapy with the concept of Water Seal Drainage (WSD), which requires a long hospital stay. Heimlich valve is a non-return valve that allows fluid and air to exit the thoracic cavity (on inspiration) and prevents fluid and air from re-entering (during expiration). Heimlich valve is a viable, inexpensive, convenient, safe, effective, and efficient alternative in the management of ambulation of patients requiring prolonged pleural cavity drainage. The use of Heimlich valve is an alternative option for patients with persistent pneumothorax or fluidopneumothorax. It can shorten the time of treatment in the hospital, lowering treatment costs, and minimize the presence of nosocomial infections. Relative contraindications include fluidopneumothorax with massive pleural effusion or empyema. The risks and complications are dislodgement or improper reattachment, leaking valve, adhesion, and blockage, thus becoming tension pneumothorax or pleural cavity infection. Currently the latest innovation also improves the patient’s convenience, like Thoracic Vent, Pneumostat, or Mini Mobile Dry Seal Drain.